Analysis of match performance of full-backs from selected European soccer leagues - Konefal, M.; Chmura, P.; Andrzejewski, M.; Pukszta, D.; Chmura, J. (Central European Journal of Sport Sciences and Medicine, 2015)
The aim of the present study was the analysis of match activities of full-backs from selected European national soccer leagues. The study sample comprised 30 full-backs playing in the autumn round of the 2014/15 season from five European national top-tier leagues: English Premier League, Spanish Primera Division, German Bundesliga, Russian Priemjer Liga and Italian Serie A. The performance of full-backs (left-back and right-back) from each selected team was analyzed using a professional match analysis system OptaPro which tracks every possible type of ball touch and on the ball action in match covered by a rigid set of definitions. The data for analysis included the total number of passes, total number of crosses, and total number of ball touches performed by the full-backs in three zones of the pitch: attack, midfield and defense. The study results showed that the full-backs from the Spanish Primera Division executed the highest number of passes and crosses as well as ball touches in the attack zone. They also performed the lowest number of passes in the midfield and defense zones, in which the highest percentage of passes was achieved by the full-backs from the German league teams. The study indicates that in modern soccer defenders must possess a high level of offensive skills that can be necessary in the last stage of a team`s attack.